A revision of Axinaea (Melastomataceae). - Morales, Carlos O. (Universidad de Costa Rica, 2015)
RESEÑA DE LIBROCotton, Elvira, Borchsenius, Finn & Balslev, Henrik. (2014).A revision of Axinaea (Melastomataceae).Copenhagen, Det Kongelige Danske Videnskabernes Selskab(The Royal Danish Academy of Sciences and Letters). Scientia Danica, Series B,  Biologica, 4, 1-120.